Arguments for abrogation in the Qur'an: A critique - Khan, Israr Ahmad (2012)
Many Muslim scholars such as Abu ‘Ubayd (d.224 A.H.), al-Nahhaas (d.377 A.H.), Makki (d.437 A.H.), Ibn al-‘Arabi (d543 A.H.), ibn al-Jawzi (d.597 A.H.), al-Zarkashi (d.794 A.H.), al-Suyuti (d.911 A.H.), al-Dehlawi (d.1176 A.H.), and al-Zurqani (d.1948 C.E.) have aggressively argued that some verses—ranging from five hundred to only five—of the Qur’an are practically invalid due to the apparent conflict between them and other verses on the same subject matter. The arguments are based on some Qur’anic verses, statements attributed to Companions, those ascribed to later generation scholars, claim about the existence of abrogated verses in the Qur’an, and the claim of Ijmaa‘ of the Muslim ummah. Some other Muslim scholars have argued to rebut the theory of abrogation in the Qur’an. The debate is still going on. The Muslim ummah stands confused over this issue. There is a need of looking at all the arguments advanced either in favor or against abrogation and analyzing them critically so as to let the clear picture emerge on the matter. This paper represents a humble attempt to carry out that delicate task. The critical analysis of the arguments will be surely based on universal principles of criticism. The objective of this paper is certainly not to discredit Muslim scholarship; it is rather to substantiate that the Qur’an in its entirety, without any exception, is all-time valid, and no command therein is ever practically invalid.